2019
DOI: 10.1308/rcsann.2018.0196
|View full text |Cite
|
Sign up to set email alerts
|

Is it always necessary to perform an axillary lymph node dissection after neoadjuvant chemotherapy for breast cancer?

Abstract: Introduction Recent prospective studies support the feasibility of performing sentinel lymph node biopsy following neoadjuvant chemotherapy in initially fine-needle aspiration cytology or ultrasound-guided biopsy-proven node-positive breast cancer. The main aid is to identify preoperative features that help us predict a complete axillary response to neoadjuvant chemotherapy in these patients and thus select the candidates for sentinel lymph node biopsy post-neoadjuvant chemotherapy to avoid unnecessary axillar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 19 publications
0
11
0
3
Order By: Relevance
“…A Spanish study published in 2018 also investigated whether axillary lymph node dissection should be performed after neoadjuvant therapy in cases where an axillary lymph node is considered positive with aspiration cytology. 34 In cases showing a significant presence of the HER2 receptor and low expression of the oestrogen receptor, there is a high chance that complete pathological remission occurs, and in these cases, ALND was not recommended. Our analyses confirmed the same result.…”
Section: Discussionmentioning
confidence: 99%
“…A Spanish study published in 2018 also investigated whether axillary lymph node dissection should be performed after neoadjuvant therapy in cases where an axillary lymph node is considered positive with aspiration cytology. 34 In cases showing a significant presence of the HER2 receptor and low expression of the oestrogen receptor, there is a high chance that complete pathological remission occurs, and in these cases, ALND was not recommended. Our analyses confirmed the same result.…”
Section: Discussionmentioning
confidence: 99%
“…But the post-NAT MRI obtained a high negative predictive value (94% and 97.3%, respectively), which means that negative post-NAT MRI can accurately exclude the axillary lymph node diseases [101,102]. Before and during NAT, lymph node pCR can be predicted by negative hormone receptor and positive HER2 receptor status [103][104][105], lower clinical T and N stage [103], higher histological/nuclear grade [103], and treatment response to NAT of breast primary lesions [106,107]. According to the study by Osorio-Silla [77], 59.7% of patients with primary lesions complete response on MRI also achieved complete response on axillary lymph node, and 75.9% of patients with non-complete response of breast primary tumors on MRI had residual lymph node disease after surgery.…”
Section: Lymph Node Response Evaluationmentioning
confidence: 98%
“…Several groups have found that adding MRI response of the primary tumor to clinicopathologic data achieves significantly better predictive power. [74][75][76][77] Ha et al trained an artificial intelligence algorithm to predict pCR in the axilla based on pretreatment MRI of the in-breast tumor alone, achieving an overall accuracy of 83%. 78 These models could improve prediction of axillary disease and allow better preoperative planning and patient counseling regarding surgical and radiation options.…”
Section: Lymph Node Evaluationmentioning
confidence: 99%
“…Negative hormone receptor and positive HER2 receptor status, lower clinical T and N stages, high histologic/nuclear grade, and breast tumor response to neoadjuvant therapy are predictors for axillary pCR. Several groups have found that adding MRI response of the primary tumor to clinicopathologic data achieves significantly better predictive power 74–77 . Ha et al trained an artificial intelligence algorithm to predict pCR in the axilla based on pretreatment MRI of the in‐breast tumor alone, achieving an overall accuracy of 83% 78 .…”
Section: Lymph Node Evaluationmentioning
confidence: 99%